Enhancement of manganese extraction in a biochar-enriched bioleaching column with a mixed culture of indigenous bacteria - Endah Retnaningrum; WAHYU WILOPO; I WAYAN WARMADA (Society for Indonesian Biodiversity, 2021)
Abstract. Retnanimgrum E, Wilopo W, Warmada IW. 2021. Enhancement of manganese extraction in a biochar-enriched bioleaching column with a mixed culture of indigenous bacteria. Biodiversitas 22: 2949-2955. Biochar can improve manganese ore extraction during bioleaching by inducing redox reactions and providing a porous matrix for bacterial attachment. In this research, the effect of variations in biochar concentration on the performance of a bioleaching column with a mixed culture of Acidithiobacillus sp. KL3 and Bacillus niacini KB3B1 were studied comprehensively for 30 days. Addition of 0.4% biochar resulted in 89% manganese extraction. Bioleaching with biochar promoted the oxidation of sulfur and yielded high sulfate concentrations, much better pH, and excellent oxidation–reduction potential conditions. The bacteria in the mixed culture survived and adapted to the extreme column environment by releasing extracellular polymeric substance, as evidenced by the sharp increase in the content of the material in the column to 135.7 mg/g over 30 days of incubation. The synergistic effect of the bacteria in the mixed culture greatly contributed to the mechanism of manganese extraction in the column, as indicated by changes in relative bacterial abundance, which is related to bacterial community succession during bioleaching. The relative abundance of B. niacini KB3B1 gradually increased and peaked at 30% over 9 days of measurements. By comparison, the abundance of Acidithiobacillus sp. KL3 first decreased over 9 days of bioleaching and then increased to a maximum of 80% in the final stages of the process. This finding reveals that biochar addition could enhance the mechanisms of bioleaching and improve the yield of manganese extraction.